STUDI ANALITIS ATAS TAFSIR AL-MANAR: KONTRIBUSI INTELEKTUAL MUHAMMAD ABDUH DAN M. RASYID RIDHA DALAM TRADISI TAFSIR MODERN - Rezwandi Rezwandi; Ahmad Fikri; Minkhatul Maula Sofa (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study aims to analytically examine the intellectual contributions of Muhammad Abduh and M. Rasyid Ridha to the tradition of modern exegesis through their monumental work, Tafsir al-Manar. This study uses a qualitative approach with a library research method, namely by examining various primary and secondary sources, both in the form of tafsir books, scientific works, and relevant contemporary research results. The results of the study show that Tafsir al-Manar was born out of a social, political, and intellectual context that demanded the renewal of Islamic thought in the modern era. The contributions of Abduh and Ridha are evident in their efforts to integrate rationality, morality, and social relevance in the interpretation of the Qur'an, thus giving birth to a paradigm of interpretation that is responsive to the changing times. Furthermore, the influence of Tafsir al-Manar has proven to be so widespread that it has inspired the emergence of modern interpretations such as Tafsir al-Maraghi and Tafsir al-Azhar, as well as providing a methodological basis for the development of contextual interpretation today. Thus, this study confirms that Tafsir al-Manar not only serves as a monumental work of interpretation, but also as an important milestone in the evolution of the modern tradition of interpretation that emphasises a balance between text, reason, and social reality.